Entrepreneurship as social change - Steyaert, Chris; Hjorth, Daniel (Cheltenham, UK ; Northamption, MA : Edward Elgar, 2006)
This book examines entrepreneurship as a societal phenomenal. It provides an in-depth study of the social aspects of entrepreneuship, illustrating how entrepreneuship affects society.
Includes bibliographical references (p. 277-316) and index.
aug 08/05/13
Loans
Keywords: Social entrepreneurship; Social change